Effectiveness of the stroke e-learning module on Malaysian doctors’ knowledge of acute ischaemic stroke management - Albart, Stephenie Ann; Yusof Khan, Abdul Hanif Khan; Abdul Rashid, Aneesa; Wan Zaidi, Wan Asyraf; Looi, Irene; Kee, Hoo Fan (Penerbit Universiti Sains Malaysia, 2024)
Background: The Stroke e-Learning Module (SEM) is a nationwide initiative to improve stroke care in Malaysia. This study aimed to assess the module’s effectiveness in improving knowledge on acute ischaemic stroke (AIS) management among Malaysian doctors. Methods: This was a pre-post study design. Medical officers, specialists and general practitioners from various disciplines who work in healthcare facilities in Malaysia were recruited virtually from those who registered for the SEM on the Docquity platform between 1 February 2021 and 31 January 2022. The Acute Stroke Management Questionnaire (ASMaQ), an existing validated questionnaire, was used to measure the doctors’ knowledge of AIS management before and after the SEM. The ASMaQ had three domains: i) general stroke knowledge (GSK), ii) hyperacute stroke management (HSM) and iii) advanced stroke management (ASM). The paired t-and the McNemar-tests were used to evaluate the effectiveness of the module. Results: One hundred and seventy-one participants voluntarily responded to the pre-and post-module questionnaires. The paired t-test revealed statistically significant improvement for the ASM knowledge scores (mean difference = 2.5; 95% CI: 1.8, 3.2; P < 0.001). The baseline proportion of participants with good knowledge of GSK, HSM and ASM were 92.4%, 64.9%, and 76%, respectively. The McNemar test showed that approximately 14% of the participants had significant improvement in ASM knowledge (P < 0.001). However, no significant changes were noted for GSK (–0.6%) and HSM (4.1%). Conclusion: The SEM has been shown to increase Malaysian doctors’ knowledge on ASM. However, greater effort should be made to improve GSK and HSM knowledge, particularly in areas related to stroke thrombolysis.